2017
DOI: 10.1097/phm.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and Electrophysiological Evaluation of Ulnar Nerve Instability and Snapping of the Triceps Medial Head in Healthy Subjects

Abstract: Ulnar nerve instability increased with elbow flexion and correlated with snapping of the triceps medial head. Ultrasonography of the ulnar nerve is an important tool in ulnar nerve instability assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 9 publications
4
45
0
Order By: Relevance
“…When investigating the interaction between the TBM and the position of the ulnar nerve in its sulcus, we found a relatively high prevalence (50%) of ulnar nerve (sub)luxation among our controls. Earlier studies using clinical testing, particularly palpation, estimated the prevalence of ulnar nerve (sub)luxation at about 30%; however, recent studies using sonography showed a prevalence of about 50%, which is in accordance with the results in our control group. This indicates a higher sensitivity of sonography in assessing ulnar nerve (sub)luxation, as suggested earlier by Okamoto and colleagues …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…When investigating the interaction between the TBM and the position of the ulnar nerve in its sulcus, we found a relatively high prevalence (50%) of ulnar nerve (sub)luxation among our controls. Earlier studies using clinical testing, particularly palpation, estimated the prevalence of ulnar nerve (sub)luxation at about 30%; however, recent studies using sonography showed a prevalence of about 50%, which is in accordance with the results in our control group. This indicates a higher sensitivity of sonography in assessing ulnar nerve (sub)luxation, as suggested earlier by Okamoto and colleagues …”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, asymptomatic cases of ulnar luxation should not be regarded as pathologic . Finally, other studies failed to establish an association between ulnar dislocation and damage by demonstrating that dislocation did not occur more frequently in patients with ulnar neuropathy, and electrodiagnostic abnormalities did not occur more frequently in subjects with ulnar nerve dislocation . In cases of asymptomatic luxation (the great majority), any therapeutic action is inappropriate .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations